Impact of climate change on water resources and potential adaptations for Indian agriculture - Sharma, Bharat R. (Annals of Agricultural Research, 2014)
Indian agriculture is the largest user of rainfall, surface and groundwater resources. Some of the large river systems feedings the canal systems and the groundwater aquifers, like the Indus, the Ganges, the Brahmaputra and their several tributaries have their origin in the Himalayas. A large part of the discharge of these river systems is fed through melting of the snow and glaciers. Although there is a lack of adequate scientific evidence on regional scales, a number of recent observational and modelling studies do suggest that the climate is changing. According to IPCC, the most significant consequences of climate change will be its impact on the hydrologic cycle, as already experienced in many parts of the world including India. Changes in precipitation intensity and duration will probably be the main factors altering the hydrologic cycle leading to more floods and droughts. Availability or scarcity of water will vary greatly depending on the region. The impact of climate change will be greater in India, where a majority of the rural population depends on agriculture for their livelihoods, and where agriculture is primarily dependent on the monsoons. Governments and communities have not been able to adequately address climate related challenges to people's livelihoods that follow from changes in water availability, loss of crops and income with the occurrence of extreme weather events like floods and droughts. After a brief introduction to the importance of the subject, this paper describes in detail the impact of climate change on water resources in India, with special reference to the Indus and the Ganges River systems which constitute the major food basket of the country. The impacts of climate change on agriculture sector, including the rainfed agriculture have been presented. An analysis of the potential opportunities presented by enhanced flows for the surface systems and recharge for the groundwater aquifers has been presented and the paper concludes by presenting adaptive mechanisms in the agriculture sector and the important recommendations for improving institutional capacity, development and management of water resources, adaptation to floods and prevention and management of droughts.